ADNP: in search for molecular mechanisms and innovative therapeutic strategies for frontotemporal degeneration - Gozes, Illana; Ivashko-Pachima, Yanina (Frontiers in Aging Neuroscience, 2015)
Activity-dependent neuroprotective protein (ADNP) is deregulated in Alzheimer’s disease (AD) and in schizophrenia and mutated in autism. In mice, ADNP is essential for brain formation and ADNP haploinsufficiency is associated with cognitive and social deficits and tauopathy. Tauopathy, a major pathology in AD, is also found in ~45% of frontotemporal dementias (FTDs). Tau transcript, a product of a single gene, undergoes alternative splicing. Tau splicing seems to be altered in FTD brain. In transgenic mice overexpressing a mutated tau in the cerebral cortex, significant increases in ADNP transcript expression were observed in the cerebral cortex of young transgenic mice (~disease onset) and a marked decrease with aging as compared to control littermates. ADNP is a member of the SWItch/Sucrose NonFermentable (SWI/SNF) chromatin remodeling complex also associated with alternative splicing, including tau transcript splicing. Further cellular interactions of ADNP include association with microtubules, with tau being a microtubule – associated protein. NAP (davundetide), a novel drug candidate derived from ADNP, increases ADNP-microtubule association and protects against tauopathy and cognitive deficiencies in mice. Although, NAP did not provide protection in progressive supranuclear palsy (PSP), a pure tauopathy, it increased cognitive scores in amnestic mild cognitively impaired patients and protected functional activity in schizophrenia patients. This mini-review focuses on ADNP in the context of FTD and tau/microtubules and proposes NAP as a novel drug target for future clinical evaluations.